Analisis Pengaruh Perbandingan Sistem Hybrid PV-Genset Menggunakan Homer Grid - Samsurizal Samsurizal; Fairakha Rezky Alfaafaa (KILAT, 2022)
95% of energy use in Indonesia is still dominated by fossil fuels. One way to meet the increasing energy needs is by using renewable energy.. The most easily available and popular renewable energy today is Solar Power Plants. Currently, solar power plants have various types to maximize their potential, one of which is the hybrid PV-genset system. This research was conducted at SMKN Central Java which has a solar power plant hybrid pv-genset system by connecting the output on grid solar power plants with generators in parallel without battery backup. The study was carried out by reviewing the fuel consumption of the generator through two scenarios without and with battery backup in the system using the HOMER Grid software to run the simulation by entering the required parameters. The results of this study indicate that the system with battery backup has 61.62% greater savings on the fuel consumption side and 61.87% more efficient on the fuel cost side to operate the generator when a blackout occurs.